Social Conflict Management through Multicultural Approach and Policy in Preventing and Overcoming the Social Disintegration - Abdullah, Sahawiah (TAWARIKH, 2014)
ABSTRACT: Indonesia is a diverse country in terms of ethnic groups and languages. However, this diversity would negatively be a threat to the existence of Indonesia. The ability of the nation-state to manage and prevent the emergence of potential threats are efforts that needs to be pursued. One of the apporaches that might support the efforts is by recognizing the importance of promoting people awareness that multiculturalism is a reality that must be faced.Â  Therefore, multiculturalism should be the basis for any implementation of the state policies. In order to enhance social resilience, the policy can be implementated through strengthening and empowering the social structures, social institutions, and social networks. It should be designed in an integrated system ranging from the scope of national to villages. With regards to the curative activities carried out for the victims of social conflicts, it should be directed toward short, medium, and long terms emergency measures; so, as the victims are able to meet their basic needs. In terms of the main executors (agents of change), the policy implementation should be directed toward any effort aimed at developing advocacy on the levels of individual, family, and group as well as community. The improvement and development of social resilience needs to be pursued in order to enhance the ability of communities to utilize resources and manage variety of public interests and social conflicts. With these efforts, the historical facts that Indonesia is consisted of various ethnic groups, languages, and diverse cultures can be truly become a positive potential to improve the development of nation, and not vice versa.KEY WORDS: Social conflict, social integration, social disintegration, multicultural, policy implementation, and Indonesian society.About the Author: Dr. Sahawiah Abdullah is a Senior Lecturer at the STIKS (Sekolah Tinggi Ilmu Kesejahteraan Sosial or College of Social Welfare Science) Tamalanrea in Makassar City, South Sulawesi, Indonesia. Corresponding author is sahawiah_depsos@yahoo.comHow to cite this article? Abdullah, Sahawiah. (2014). âSocial Conflict Management through Multicultural Approach and Policy in Preventing and Overcoming the Social Disintegrationâ in TAWARIKH: International Journal for Historical Studies, Vol.5(2) April, pp.237-246. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia] and UVRI [Universitas Veteran Republik Indonesia], ISSN 2085-0980.Chronicle of the article: Accepted (February 17, 2014); Revised (March 20, 2014); and Published (April 28, 2014).